FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN KENDARAAN BERMOTOR RODA DUA DI KOTA PEKANBARU 2011-2019 - Damanik Manuel Jansef; Syapsan Syapsan; Tampubolon Dahlan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Transportation is a major component in living and living systems, government systems, and social systems. The socio-demographic conditions of the region have an influence on the transportation performance in the region. The level of population density will have a significant influence on the ability of transportation to serve the needs of the community. In urban areas, the trend is a high population growth due to birth rates and urbanization. The level of urbanization has implications for the increasingly dense population which directly or indirectly reduces the competitiveness of regional transportation (Susantoro, 2004).This study aims to analyze the factors that influence the growth of two-wheeled motorized vehicles in Pekanbaru City 2011-2019. The population of this study is Population Growth, Economic Growth, and Road Conditions in Pekanbaru City 2011-2019 from the BPS Riau Province and the Riau Provincial Transportation Service. Data analysis is one of the stages of research activities in the form of the process of compiling and managing data. The data analysis method used in this research is quantitative data analysis method. While the analytical tool used in this study is a multiple linear regression analysis model with the help of SPSS Software Version 23 for windows. Based on the results of the analysis it was found that population has a positive effect on the number of growth of twowheeled vehicles, economic growth has a positive effect on the number of growth of two-wheeled vehicles and the length of the road has no effect on the number of growth of two-wheeled vehicles.Keywords : Economic Growth (X.1), Population (X.2), Road Length (X.3), Motor Vehicle Growth (Y)